2013
DOI: 10.1002/ar.22786
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenic and Tissue Remodeling Factors in the Prostate of Elderly Rats Submitted to Hormonal Replacement

Abstract: The influence of senescence and hormone replacement on the onset of pathologic processes in the prostate is not yet fully understood. The aim was to identify the immunoreactivity and protein levels of molecules involved in cell proliferation, tissue remodeling and angiogenesis in the ventral prostate of elderly rodents following hormonal replacement. Male Sprague-Dawley rats were separated into one Young group (4-months old), treated with peanut oil (5 mL kg 21 , s.c.), and six Senile groups. The senile rats (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 76 publications
0
5
0
2
Order By: Relevance
“…This life period is associated with significant hormonal changes in the prostate, characterized by progressive estradiol accumulation and a simultaneous decrease of androgen levels as well as reduced prostatic sensitivity to androgenic actions . Several studies have demonstrated structural and paracrine signaling alterations in the prostate during late life due to hormonal imbalance . Accordingly, Hetzl et al reported that the enhancement of this imbalance by promoting hormonal ablation led to increased fibroblast growth factor (FGF) signaling in the prostatic microenvironment of aged rats, pointing to a possible androgen‐independent FGF activation.…”
Section: Introductionmentioning
confidence: 99%
“…This life period is associated with significant hormonal changes in the prostate, characterized by progressive estradiol accumulation and a simultaneous decrease of androgen levels as well as reduced prostatic sensitivity to androgenic actions . Several studies have demonstrated structural and paracrine signaling alterations in the prostate during late life due to hormonal imbalance . Accordingly, Hetzl et al reported that the enhancement of this imbalance by promoting hormonal ablation led to increased fibroblast growth factor (FGF) signaling in the prostatic microenvironment of aged rats, pointing to a possible androgen‐independent FGF activation.…”
Section: Introductionmentioning
confidence: 99%
“…In the prostate, androgens are required for normal development and function. However, the role of oestrogens in normal prostate development is ill defined, as biochemical mechanisms are still under investigation; the current dogma being that oestrogens are involved in the differentiation of epithelial tissue (Chen et al 2012, Francis et al 2013) and regulation of prostatic angiogenesis (Montico et al 2013).…”
Section: Sex Steroids and Prostate Cancermentioning
confidence: 99%
“…These molecules can be secreted by the tumor and/or stromal cells, or mobilized from the extracellular matrix (Tuxhorn et al, 2001;Van Moorselaar and Voest, 2002;Condon, 2005). The vascular endothelial growth factor (VEGF), which is considered the most potent mediator of angiogenesis and endothelial cell functions, stimulates endothelial cell proliferation, differentiation and migration, and promotes increased vascular permeability (Van Moorselaar and Voest, 2002;Montico et al, 2013;Li et al, 2023).…”
Section: Introductionmentioning
confidence: 99%